Systematic review on citizens' literacy in omic sciences and web search of initiatives to improve it. (30th September 2020) - Sassano, M; Calabrò, G E; Tognetto, A; Federici, A; Ricciardi, W; Boccia, S
Abstract: Introduction: We are assisting to a progressive change in the classical approach to patient care toward so-called personalized medicine, mainly driven by the development of omic sciences. To implement omic sciences into practice it is important to address healthcare professionals', policy makers', leaders', and citizens' literacy Methods: As part of a project funded by the Italian Centre for Disease Prevention and Control (CCM), we carried out a systematic review (SR) on citizens' attitude, knowledge, and educational needs in omic sciences. The search was carried out on Pubmed, Web of Science, and Embase. We also conducted a separate web search on Google, Yahoo, and Bing on initiatives published in Italian and English aimed at improving citizens' literacy in the same field. Websites of retrieved initiatives were examined to identify additional resources Results: Forty-nine studies were included in the SR. Most studies (n = 26, 66.7%) reported low levels of knowledge in omic sciences among citizens, and conflicting attitudes related to potential risks and benefits of omic sciences. Eleven studies (22%) evaluated citizens' educational needs, and most (n = 9, 82%) reported a clear knowledge gap. As for the web search, 13 initiatives were identified in Italy, 4 in Europe, and 22 in non-European Countries. Overall, 33% of them required in-person attendance, while 67% were web-based resources. The former included exhibitions, seminars, courses, symposia, information stands in public places, guided visits at research laboratories, and interactive laboratories; the latter included web-pages for reading, online lessons and courses, web portals for information, videos and short movies, animations, apps for mobile devices Conclusions: Results show a clear need to improve citizens' literacy. To achieve this goal, the implementation of effective strategies and initiatives is crucial, hence this effort to summarize the existing ones will be essential for future plan developments. Key messages: The current challenge is to identify effective methods of improving citizens' literacy and implementing them. Only through citizens' empowerment the implementation of omic sciences in the Health System will be possible, since citizens are increasingly active in the health context.